2018
DOI: 10.1038/s41591-018-0202-8
|View full text |Cite
|
Sign up to set email alerts
|

Precision identification of diverse bloodstream pathogens in the gut microbiome

Abstract: A comprehensive evaluation of every patient with a bloodstream infection includes an attempt to identify the infectious source. Pathogens can originate from various places, such as the gut microbiome, skin, and external environment. Identifying the definitive origin of an infection would enable precise interventions focused on management of the source 1 , 2 . Unfortunately, hospital infection control practices are often informed by assumptions about the sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 51 publications
(51 reference statements)
10
105
0
Order By: Relevance
“…Recent publications, such as that from Tamburini et al (2018), highlight the importance of using powerful genomic tools such as WGS for strain tracking and more precise identification of the origins of BSIs, in order for hospitals and health care providers to most effectively work to prevent infections. Here WGS was used successfully as a predictive tool for the antimicrobial resistance profile of the B. cereus CVC_S1 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications, such as that from Tamburini et al (2018), highlight the importance of using powerful genomic tools such as WGS for strain tracking and more precise identification of the origins of BSIs, in order for hospitals and health care providers to most effectively work to prevent infections. Here WGS was used successfully as a predictive tool for the antimicrobial resistance profile of the B. cereus CVC_S1 strain.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to bacterial complications, Taur et al performed a study of 94 allogeneic hematopoietic stem cell transplant (HSCT) recipients and reported that Enterococcus gut domination increased the risk for future development of Enterococcus sepsis by 9‐fold . In a different cohort of allogeneic HSCT recipients, Tamburini et al did a strain level analysis on bloodstream isolates and reported that strains of Escherichia coli and Klebsiella pneumoniae that caused septicemia likely originated from the gut …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite all efforts using hygiene, asepsis, antisepsis and antibiotics, SSI occur in one-tenth of all patients undergoing surgery (3,4). Our studies demonstrate the mechanistic basis for the observation that SSI as well as sepsis have an intestinal microbial signature (24,48). These findings emphasize that the prevention of SSIs requires further understanding of the communication between the intestinal microbiome and systemic host responses.…”
Section: Discussionmentioning
confidence: 52%
“…This was not dependent on the intestinal microbial composition given that the bacterial species identified in the liver, spleens, MLNs and lungs of Rag2 -/-Il2r -/mice mainly included Escherichia coli, Enterococcus faecalis and Enterobacter hormaechei and to a lesser abundance Staphylococci ss, which are all members of the intestinal microbiota ( Fig. S4f-i) (24). We next assessed the effect of intestinal bacterial dissemination on proliferative hepatocyte indices, which are the most relevant outcome parameters after hepatic surgery.…”
Section: Major Liver Surgery Provokes Intestinal Microbial Translocatmentioning
confidence: 93%